Antibacterial Activity of the Chloroform, Acetone, Methanol and queous Extracts of Algerian Lichens - Rafika, Brakni; Monia, Ali (Jordan Journal of Pharmaceutical Sciences, 2018)
In the current study, we investigated the antibacterial activity of chloroform, acetone, methanol and aqueousextracts of the following lichens: Evernia prunastri (L.) Ach., Ramalina fastigiata (Pers.) Ach. and Cladoniarangiformis Hoffm. The phytochemical analyses of extracts of each species were determined by thin layerchromatography (TLC) and microcrystallization. These extracts were tested in vitro against Escherichia coli,Klebsiella pneumonia, Staphylococcus aureus, Proteus mirabilis and Pseudomonas aeruginosa by the discdiffusion method.The sensitivity of the bacteria to the different lichen extracts is as follows: Staphylococcus aureus is highlysensitive to all extracts and more precisely to the methanolic extract of Evernia prunastri (with a 43 mm inhibitionzone), Escherichia coli particularly sensitive to the chloroformic and acetonic extracts of E prunastri and Rfastigiata and to the methanolic and aqueous extracts of C rangiformis, Klebsiella pneumonia is insensitive to alllichen extracts, Proteus mirabilis and Pseudomonas aeruginosa are slightly sensitive to certain extracts of Rfastigiata.The activity of the lichenic extracts was certainly due to predominant compounds such as lichenic acids (Usnicacid, Evernic acid, Fumarprotocetraric acid and Atranorin), some of which have already proved their antibacterialefficacy. Therefore, these lichens may be used to discover bioactive products that may serve as new sources ofnatural antimicrobial agents.